Gamebooks and branching narratives in education: fostering sustainability competences to promote positive social change - Fenici, Marco; Mosca, Ivan (Frontiers in Education, 2024)
Gamebooks and branching narratives are a specific form of interactive literature that allows the reader to participate in the story, making decisions that affect its final outcome. We describe one case-study of introducing branching stories in the context of higher education, and discuss how it possibly enhanced communication and collaboration skills as well as prosocial attitudes. We further generalize this experience to discuss how educators can use branching narratives to promote positive social change. To this aim, we clarify what social development and sustainability competences are, and show how educational activities based on branching narratives can effectively promote their acquisition.